Towards comprehension of complex chemical evolution and diversification of terpene and phenylpropanoid pathways in Ocimum species - Singh, Priyanka; Kalunke, Raviraj M.; Giri, Ashok P. (RSC Advances, 2015)
Ocimum species present a wide array of diverse secondary metabolites possessing immense medicinal and economic value. The importance of this genus is undisputable and exemplified in the ancient science of Chinese and Indian (Ayurveda) traditional medicine. Unlike several other plant species of Artemisia, Salvia, Catharanthus, Taxus, Mentha, etc. that are largely exploited, detailed characterization and identification of important metabolites from Ocimum species remained unexplored. Till date, most of the analyzed Ocimum species are predominantly rich in either phenylpropanoids or terpenoids. Metabolite data suggests domination of a unique set of signature compounds in all species. However, molecular pathways leading to the production, accumulation and metabolism of these compounds are poorly understood. The past few years have witnessed an upsurge in our understanding of the complex and intricately woven secondary metabolic pathways. Such information is generated through systematic analysis and correlation of metabolite profiling with transcriptomics data sets from different Ocimum species. The present review is aimed at integrating our current knowledge to understand the active secondary metabolic pathways, the key players in flux regulation including external stimuli, differential gene expression, transcription factors, microRNAs, enzyme promiscuity, etc. Extensive analysis of available data identifies events that may have contributed to evolve Ocimum species rich with a specific set of metabolites, thus, shedding light on pathway diversification. We believe that a better understanding of the multi-level regulation of intermediates and metabolites will help us harness the inherent diversity of Ocimum species optimally.

Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Comprehensive metabolic and transcriptomic profiling of various tissues provide insights for saponin biosynthesis in the medicinally important Asparagus racemosus - Srivastava, Prabhakar Lal; Shukla, Anurag; Kalunke, Raviraj M. (Scientific Reports, 2018)
Asparagus racemosus (Shatavari), belongs to the family Asparagaceae and is known as a "curer of hundred diseases" since ancient time. This plant has been exploited as a food supplement to enhance immune system and regarded as a highly valued medicinal plant in Ayurvedic medicine system for the treatment of various ailments such as gastric ulcers, dyspepsia, cardiovascular diseases, neurodegenerative diseases, cancer, as a galactogogue and against several other diseases. In depth metabolic fingerprinting of various parts of the plant led to the identification of 13 monoterpenoids exclusively present in roots. LC-MS profiling led to the identification of a significant number of steroidal saponins (33). However, we have also identified 16 triterpene saponins for the first time in A. racemosus. In order to understand the molecular basis of biosynthesis of major components, transcriptome sequencing from three different tissues (root, leaf and fruit) was carried out. Functional annotation of A. racemosus transcriptome resulted in the identification of 153 transcripts involved in steroidal saponin biosynthesis, 45 transcripts in triterpene saponin biosynthesis, 44 transcripts in monoterpenoid biosynthesis and 79 transcripts in flavonoid biosynthesis. These findings will pave the way for better understanding of the molecular basis of steroidal saponin, triterpene saponin, monoterpenoids and flavonoid biosynthesis in A. racemosus.

Detection of ciprofloxacin residues in cow milk: a novel and rapid optical beta-galactosidase-based screening assay - Kalunke, Raviraj M.; Grasso, Gerardo; D'Ovidio, Renato; Dragone, Roberto; Frazzoli, Chiara (Microchemical Journal, 2018)
Ciprofloxacin (a member of the fluoroquinolone class) is one of the most widely used antibacterial agents for the treatment of bacterial infections in livestock. The improper use of such antibacterial agents could lead to the presence of residues in animal origin foods (including milk) and consequently harmful effects for health of consumers, together with the spread of antibiotic-resistant bacterial strains. Therefore, in order to support good farming practices and to ensure food safety, antimicrobial (in particular fluoroquinolones) residues surveillance through improved monitoring techniques is crucial. However, commercial available kits for the detection of fluoroquinolones residues in food samples are time-consuming and still fail to detect MRL concentrations for fluoroquinolones (e.g. 0.1 mg/kg for the sum of enrofloxacin and ciprofloxacin residues). Here a novel and rapid assay for ciprofloxacin residual detection through optical microbiological screening in commercially pasteurized cow's milk samples is described. Escherichia coli ATCC 11303 cell proliferation was optically monitored by measuring endogenous (beta-gal activity that was determindd through colorimetric assay in the presence of a chromogenic beta-gal artificial substrate. Optical density of E. coli cell culture (linked to cell proliferation) was positively correlated with endogenous beta-gal activity. As the presence of ciprofloxacin residues inhibits the E. coli cell proliferation in tested samples, (3-gal levels decreased more in exposed samples than in control. The essential step of beta-gal induction (usually obtained by IPTG) was obtained by exploiting the lactose present in the milk. Our findings show a detection of ciprofloxacin residues at 1 MRL concentration after 1 h using ONPG as chromogenic 3 gal artificial substrate and lactose as (3-gal inducer. Compared to previously described methods, this assay proved to be a rapid, proficient and more eco-friendly (i.e. minimizing the use of additional reagents) system that could be potentially employed as screening method for detection ciprofloxacin residues in cow's milk. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Antibiotic resistance; Farm animals; Fluoroquinolones; HACCP; One health; Primary production; Risk assessment and management

Structural, functional and evolutionary diversity of 4-coumarate-CoA ligase in plants - Lavhale, Santosh G.; Kalunke, Raviraj M.; Giri, Ashok P. (Planta, 2018)
Main conclusions The 4-coumarate-CoA ligases (4CL) contribute in channelizing flux of different phenylpropanoid biosynthetic pathways. Expression of 4CL is optimized at developmental stages and in response to environmental triggers such as biotic and abiotic stresses. The enzyme is valuable in metabolic pathway engineering for curcuminoids, resveratrol, biofuel production and nutritional improvement. Vigorous analysis of regulation at functional and expression level is obligatory to attain efficient commercial production of candidate metabolites using 4CL. Phenylpropanoid pathway provides precursors for numerous secondary metabolites in plants. In this pathway, 4-coumarate-CoA ligase (EC 6.2.1.12, 4CL) is the main branch point enzyme which generates activated thioesters. Being the last enzyme of three shared common steps in general phenylpropanoid pathway, it contributes to channelize precursors for different phenylpropanoids. In plants, 4CL enzymes are present in multiple isoforms and encoded by small gene family. It belongs to adenylate-forming enzyme family and catalyzes the reaction that converts hydroxy or methoxy cinnamic acid derivatives to corresponding thioesters. These thioesters are further utilized for biosynthesis of phenylpropanoids, which are known for having numerous nutritional and medicinal applications. In addition, the 4CL enzymes have been characterized from various plants for their role in plant physiology or in biotic and abiotic stresses. Furthermore, specific isoforms are differentially regulated upon exposure to diverse stimuli leading to flux diversion toward the particular metabolite biosynthesis. Evolutionary studies showed that 4CL separately evolved after monocot and dicot segregation. Here, we provide a comprehensive review on 4CL, which includes evolution, function, gene/protein structure, role in metabolite biosynthesis and cellular partition, and their regulation. Based on the available data, we have explored the scope for pathway engineering by utilizing 4CL enzymes.

Biosynthesis and tissue-specific partitioning of camphor and eugenol in Ocimum kilimandscharicum - Singh, Priyanka; Kalunke, Raviraj M.; Shukla, Anurag; Tzfadia, Oren; Thulasiram, V. Hirekodathakallu; Giri, Ashok P. (Phytochemistry, 2020)
In Ocimum kilimandscharicum, the relative volatile composition of camphor in leaves was as high as 55%, while that of eugenol in roots was 57%. These metabolites were differentially partitioned between the aerial and root tissues. Global metabolomics revealed tissue-specific biochemical specialization, evident by the differential distribution of 2588 putative metabolites across nine tissues. Next-generation sequencing analysis indicated differential expression of 51 phenylpropanoid and 55 terpenoid pathway genes in aerial and root tissues. By integrating metabolomics with transcriptomics, the camphor biosynthesis pathway in O. kilimandscharicum was elucidated. In planta bioassays revealed the role of geranyl diphosphate synthase (gpps) and borneol dehydrogenase (bdh) in camphor biosynthesis. Further, the partitioning of camphor was attributed to tissue-specific gene expression of both the pathway entry point (gpps) and terminal (bdh) enzyme. Unlike camphor, eugenol accumulated more in roots; however, absence of the eugenol synthase gene in roots indicated long distance transport from aerial tissues. In silico co-expression analysis indicated the potential involvement of ATP-binding cassette, multidrug and toxic compound extrusion, and sugar transporters in eugenol transport. Similar partitioning was evident across five other Ocimum species. Overall, our work indicates that metabolite partitioning maybe a finely regulated process, which may have implications on plant growth, development, and defense.
Keywords: Borneol dehydrogenase; Camphor; Eugenol; Geranyl diphosphate synthase; Lamiaceae; Metabolite partitioning; Metabolomics; Ocimum kilimandscharicum; Transcriptomics

Recent advances in plant nanobionics and nanobiosensors for toxicology applications - Ansari, Mohammad Hasan Dad; Lavhale, Santosh; Kalunke, Raviraj M.; Srivastava, Prabhakar L.; Pandit, Vaibhav; Gade, Subodh; Yadav, Sanjay; Laux, Peter; Luch, Andreas; Gemmati, Donato; Zamboni, Paolo; Singh, Ajay Vikram (Current Nanoscience, 2020)
Emerging applications in the field of nanotechnology are able to solve a gamut of problems surrounding the applications of agroecosystems and food technology. Nano Engineered Material (NEM) based nanosensors are important tools for monitoring plant signaling pathways and metabolism that arc nondestructive, minimally invasive, and can provide real-time analysis of biotic and abiotic threats for better plant health. These sensors can measure chemical flux even at the single molecule level. Therefore, plant health could be monitored through nutrient management, disease assessment, plant hormones level, environmental pollution, etc. This review provides a comprehensive account of the current trends and practices for the proposed NEM related research and its (i) structural aspect, (ii) experimental design and performance as well as (iii) mechanisms of field application in agriculture and food system. This review also discusses the possibility of integration of data from NEM based nanosensors in current and emerging trends of precision agriculture, urban farming, and plant nanobionics to adopt a sustainable approach in agriculture,
Keywords: agro-ecosystems; engineered nanomaterials; nanobionics; Nanosensors; nanotechnology; nanotoxicology